PENGEMBANGAN BAHAN AJAR IPA TERPADU TIPE INTEGRATED TOPIK NAVIGASI MIGRASI HEWAN DALAM MENINGKATKAN PENGUASAAN KONSEP DAN KETERAMPILAN PROSES SAINS SISWA - Yusup, Maulana (2017)
The objective of this study is to find out the readability and feasibility of Integrated Science Teaching Materials, learning proses using the teaching materials, the improvement of students' concept and skill of science processes, students' and teacher's responses towards the Integrated Science teaching materials in the topic of navigation of animal migration. This study was conducted to 9th grade students in one of Junior High School in Cianjur Regency in academic year 2016/2017. The research method in this study is mix methods embedded experimental design researchby combining quantitative and qualitative data. This study employed two classes; students in experimental class used Integrated Science Teaching Materials, while students in control class used the book available at school. The research instruments used in this study were instrument of teaching material readability (cloze test) and teaching material feasibility for the aspect of: content, presentation, material and validity, questions of concept mastery and skill of science process, questionnaire of teacher's and students' responses to the teaching materials. The rest result of teaching material readability was 82% and classified into independent category, meaning that the teaching materials can be used in the learning process. The test result of feasibility of content, presentation, material and validity was 71%, meaning that the quality of teaching materials is classified into very appropriate category. Data analysis on the concept and students' skill mastery shows significant difference between experimental and control classes seen from the P-value of 0.001 which is lower than 0.05. Students' responses to the Integrated Science Teaching Materials show that they are fond to use it since it is easy to learn and improving the attitude of caring the environment and curiosity. Meanwhile, teacher's responses to the Integrated Science Teaching Materials show that generally the teaching materials are easy to use. Keywords: teaching materials, Integrated Science, student concept mastery, student skill of science process, navigation of animal migration, Penelitian ini bertujuan untuk mengetahui keterbacaan dan kelayakan bahan ajar IPA terpadu tipe integrated, proses pembelajaran menggunakan bahan ajar, peningkatan penguasaan konsep dan keterampilan proses sains siswa, tanggapan siswa dan guru terhadap bahan ajar IPA Terpadu tipe integrated pada topik navigasi migrasi hewan. Penelitian ini dilakukan pada siswa kelas IX di salah satu SMP di Kabupaten Cianjur pada tahun akademik 2016/2017. Metode yang digunakan adalah mix methods embedded experimental design research dengan menggabungkan data kualitatif dan data kuantitatif. Penelitian ini menggunakan dua kelas, siswa pada kelas eksperimen menggunakan bahan ajar IPA terpadu tipe integrated,sedangkan siswa kelas kontrol menggunakan buku yang ada di sekolah. Instrumen penelitian yang digunakan berupa instrumen keterbacaan bahan ajar (tes rumpang) dan kelayakan bahan ajar yang terdiri dariAspek:isi, penyajian, materi dan kebahasaan, soalpenguasaankonsep dan keterampilan proses sains, angkettanggapansiswadan guru terhadapbahan ajar. Hasil uji keterbacaan bahan ajar sebesar 82% kategori independen. Artinya bahan dapat digunakan dalam pembelajaran. Pada uji kelayakan isi,penyajian, materidankebahasaanadalah 71%. Hal ini menjadikan kualitas bahan ajar termasukdalamkategorisangat layak. Analisis data pada penguasaankonsepdan keterampilan proses siswa terdapat perbedaan yang signifikan antara kelasekperimen dan kelas kontrol dilihat dari nilai P-Value 0,001 yang lebih kecil dari 0,05. Tanggapansiswaterhadapbahan ajar IPA Terpadutipeintegratedinimerasa senang dalam menggunakannya, mudah dipelajari, lebih meningkatkan sikap peduli lingkungan,rasa ingin tahu. Tanggapan guru terhadap bahan ajar ini secara garis besar bahwa bahan ajar ini dapat digunakan dengan mudah. Kata-kata kunci: bahan ajar, IPA terpadu tipe integrated, penguasaan konsep siswa, keterampilan proses sains siswa, navigasi migrasi hewan